Words Are Weapons : Inside ISIS's Rhetoric of Terror - Salazar, Philippe-Joseph (Yale University Press, 2017)
ISIS wages war not only on the battlefield but also online and in the media. Through a close examination of the words and images ISIS uses, with particular attention to the "digital Caliphate" on the web, Philippe-Joseph Salazar theorizes an aesthetic of ISIS and its self-presentation. As a philosopher and historian of ideas, well versed in both the Western and the Islamic traditions, Salazar posits an interpretation of Islam that places speech - the profession of faith - at the center of devotion and argues that evocation of the simple yet profound utterance of faith is what gives power to the rhetoric that ISIS and jihadists employ. At the same time, Salazar contends that Western discourse has undergone a "rhetorical disarmament." To win the fight against ISIS and Islamic extremism, Western democracies and their media, politicians, and counterterrorism agencies must consider radically changing their approach to Islamic extremism. -- from dust jacket.